Simultaneous multimodal measures for aesthetic evaluation of furniture color and form - Yaohui Ji; Yao Sun; Song Qiu; Xiaojie Geng (Scientific Reports)
Abstract The tendency toward the aesthetic preference affects an individual’s intention to purchase furniture. Color and form are two fundamental elements of furniture appearance. However, there is a significant lack of human–computer interaction research on the aesthetic evaluation of furniture with various colors and forms, necessitating a comprehensive study to provide theoretical and empirical support to furniture designers and businesses. Thus, this study introduces a multimodal method by integrating various modalities, which allowed us to investigate the factors that significantly affect subjective preference evaluation and physiological feedback. The results indicated significant correlations between behavioral data, first fixation duration, and average pupil diameter. Meanwhile, the correlation between multimodal measurement data and product aesthetic ratings was analyzed, and an evaluation model of the leisure chair aesthetic correlation mechanism was proposed.